Acute pharmacological profile of 2C-B-Fly-NBOMe in male Wistar rats—pharmacokinetics, effects on behaviour and thermoregulation - Syrová, Kateřina; Šíchová, Klára; Danda, Hynek; Lhotková, Eva; Jorratt, Pascal; Pinterová-Leca, Nikola; Vejmola, Čestmír; Olejníková-Ladislavová, Lucie; Hájková, Kateřina; Kuchař, Martin; Horáček, Jiří; Páleníček, Tomáš (Frontiers in Pharmacology, 2023)
N-2-methoxy-benzylated („NBOMe“) analogues of phenethylamine are a group of new psychoactive substances (NPS) with reported strong psychedelic effects in sub-milligram doses linked to a number of severe intoxications, including fatal ones. In our present work, we provide a detailed investigation of pharmacokinetics and acute behavioural effects of 2C-B-Fly-NBOMe (2-(8-bromo-2,3,6,7-tetrahydrobenzo[1,2-b:4,5-b′]difuran-4-yl)-N-[(2-methoxybenzyl]ethan-1-amine), an analogue of popular psychedelic entactogen 2C-B (4-Bromo-2,5-dimethoxyphenethylamine). All experiments were conducted on adult male Wistar rats. Pharmacokinetic parameters of 2C-B-Fly-NBOMe (1 mg/kg subcutaneously; s. c.) in blood serum and brain tissue were analysed over 24 h using liquid chromatography-mass spectrometry (LC/MS). For examination of behavioural parameters in open field test (OFT) and prepulse inhibition (PPI) of acoustic startle reaction (ASR), 2C-B-Fly-NBOMe (0.2, 1 and 5 mg/kg s. c.) was administered in two temporal onsets: 15 and 60 min after administration. Thermoregulatory changes were evaluated in individually and group-housed animals over 8 h following the highest dose used in behavioural experiments (5 mg/kg s. c.). Peak drug concentrations were detected 30 and 60 min after the drug application in serum (28 ng/ml) and brain tissue (171 ng/g), respectively. The parental compound was still present in the brain 8 h after administration. Locomotor activity was dose-dependently reduced by the drug in both temporal testing onsets. ASR was also strongly disrupted in both temporal onsets, drug’s effect on PPI was weaker. 2C-B-Fly-NBOMe did not cause any significant thermoregulatory changes. Our results suggest that 2C-B-Fly-NBOMe penetrates animal brain tissue in a relatively slow manner, induces significant inhibitory effects on motor performance, and attenuates sensorimotor gating. Its overall profile is similar to closely related analogue 2C-B and other NBOMe substances.